Pengaruh Konten Gaya Bahasa Campuran Indonesia-Inggris Terhadap Minat Konsumsi Tiktok @joviadhigunahunter (Survei Followers TikTok @joviadhigunahunter) - Sari, Wina Puspita; Putriana, Muria; Artoma, Nazili Lukluana; Pinkan, Sabrine; Khansa, Najwa Aulia; Avida, Caneyta Naeqris; Putri, Windy Amelia; Clarissa, Joanna Atha; Callula, Afiyah Disa; Putra, Gagak Indra (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to examine the effect of mixed Indonesian–English language style in TikTok content on the consumption interest of @joviadhigunahunter’s followers. A quantitative method with an explanatory approach was used. A sample of 100 respondents was selected using simple random sampling from a total population of 279,300 followers. Data were collected via a 4-point Likert scale questionnaire and analyzed using Pearson Product Moment validity test, Cronbach’s Alpha reliability test, and simple linear regression. The results show that most respondents are aware of and accept the mixed language style, and still find the content easy to understand and enjoyable. However, regression analysis shows a significant negative effect (significance value 0.000 < 0.05; coefficient –1868), indicating that higher use of mixed language style correlates with decreased audience interest. This may be due to potential fatigue or a sense of linguistic exclusivity. While the style can attract attention and foster limited emotional connection, its use should align with audience characteristics. Adaptive communication strategies are needed to keep content relevant and sustain long-term engagement.